2011
DOI: 10.5754/hge09721
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Delayed Gastric Emptying in Pancreaticogastrostomy by a Modified Subtotal-Stomach-Preserving Pancreaticoduodenectomy: Oida Modification

Abstract: We consider that our reconstruction procedure is useful for preventing DGE in patients who have undergone SSPPD with PG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Two of these 13 articles were excluded because they did not fulfil the inclusion criteria. Finally, three RCTs, two from Japan and one from Germany, involving a total of 418 patients, and eight non‐randomized studies, six from Japan, one from China and one from Germany, involving 574 patients, were included in qualitative and quantitative syntheses.…”
Section: Resultsmentioning
confidence: 99%
“…Two of these 13 articles were excluded because they did not fulfil the inclusion criteria. Finally, three RCTs, two from Japan and one from Germany, involving a total of 418 patients, and eight non‐randomized studies, six from Japan, one from China and one from Germany, involving 574 patients, were included in qualitative and quantitative syntheses.…”
Section: Resultsmentioning
confidence: 99%
“…A total of nine publications published between 2007 and 2014 matched the criteria for inclusion in the present meta‐analysis and were therefore reviewed . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pylorus‐resecting pancreaticoduodenectomy (PrPD), a procedure that includes resection of the duodenum and pyloric ring, was introduced as an alternative to PpPD in Japan in the 1990s and is intended to maintain gastric pooling ability and reduce the incidence of DGE. However, studies comparing rates of DGE between PrPD and PpPD have been relatively limited and have yielded conflicting results . Therefore, the benefit of PrPD remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the PROPP study are in contrast with those of most existing publications regarding the association of DGE and pylorus resection. Most nonrandomized studies 14,16,[22][23][24][25][26] have concluded that resection of the pylorus is favorable regarding DGE. In 2 nonrandomized studies 13,27 there was no difference between the 2 techniques regarding DGE.…”
Section: Discussionmentioning
confidence: 99%